Is There Evidence of Health Risks From Exposure to Micro- and Nanoplastics in Foods? - Molina, Elena; Benedé, Sara (Frontiers in Nutrition, 2022)
The human health impact of exposure to micro (MP) and nanoplastics (NP) from food remains unknown. There are several gaps in knowledge that prevent a complete risk assessment of them. First, the fact that some plastics may be chemically harmful, either directly toxic themselves or because they absorb and carry other components, which makes these particles may possess 3 types of hazards, physical, chemical and biological. In addition, the levels at which toxic effects may occur are unknown and there is a lack of studies to estimate the levels to which we are exposed. Plastic particles can induce physical stress and damage, apoptosis, necrosis, inflammation, oxidative stress and immune responses, which could contribute to the development of diseases such as cancer, metabolic disorders, and neurodevelopmental conditions, among others. In addition, they may have effects on other pathologies that have not yet been studied, such as food allergy, where they could act modifying the digestibility of food allergens, increasing intestinal permeability, promoting an intestinal inflammatory environment or causing intestinal dysbiosis, which could promote food allergen sensitization. However, given the limited information on the presence of MP and especially NP in food, further research is needed to estimate whether they could amplify the risk of allergic sensitisation to food proteins and to elucidate the risk to human health.